Ideas, Creativity, and Innovation, Critical Points for New Entrepreneurs - Prijambodo Prijambodo; R Taufik Hidayat; Eddy Setyanto; Frengki Panangiyan (STIE Tri Bhakti, 2025)
Indonesian cooperatives have developed for 77 years since independence, or 126 years if traced to the first cooperative in 1898. The repositioning of cooperative development policy began in 1978 with the establishment of the Junior Minister of Cooperatives, later becoming the Department of Cooperatives in 1983, and can be divided into two stages: 1978–1999 and 2000–present. In the first stage, policies emphasized rural development through Village Unit Cooperatives (KUD) under Presidential Instruction No. 4/1984. Since 2000, following Presidential Instruction No. 18/1999, cooperative development shifted to an open model, resulting in significant growth from 52,458 units in 1977 to 103,077 units. By 2024, 89% of cooperatives are small and micro-scale, while only 11% are medium and large. In contrast, global cooperatives have transformed into New Generation Cooperatives (NGC), emphasizing federations, innovative business models, and multi-stakeholder membership. This study highlights four policy recommendations: repositioning cooperative goals, differentiating policy for small and large cooperatives, adapting to global cooperative models, and strengthening regulations to support sustainable development.